An investigation of data analysis method for hydraulic fracturing based on the water hammer effect - Jianguo Shen; Huaiyin He; Yanchao Li; Longqing Zou; Yixuan Wang; Zhaoying Zhu; Lingkong Guo; Shuoran Fu (Unconventional Resources, 2023)
Hydraulic fracturing plays a crucial role in the development of unconventional resources, and assessing fracture geometry is a fundamental aspect of hydraulic fracturing analysis. Among the various technologies for evaluating fracture geometry, the water percussion signal-based method has gained popularity due to its cost-effectiveness, convenience, and real-time capabilities. In this study, we present a methodology for analyzing fracture data that utilizes the water percussion effect. By leveraging the impact of fractures on water percussion pressure attenuation, we propose an inverse calculation approach to determine fracture geometry. Firstly, we introduce the RCI (Reservoir-Completion-Interaction) circuit model, which effectively addresses the bottom hole fracture boundary and simulates the variation of water percussion pressure in the wellbore. Secondly, the simulation results are utilized in an iterative process to determine the RCI values, which are then utilized for the inversion calculation of fracture geometry. Finally, we apply this method to a field case and compare the simulation results with microseismic monitoring data. A larger resistance (R) value indicates a smaller fracture volume, while the (C) value can be used to monitor any poorly performing stages of the fracturing simulation process. The (I) value primarily affects the parameter calculation of the fracture size, especially the fracture width. The results of the field application show that the accuracy rate exceeding 80%, validating the reliability of the model and providing a valuable reference for field fracturing data analysis.